An Empirical Study Of Indian Private Insurance Companies: A Management Prospective - Dr. Preeti Mishra , Prof. Manoj Kumar Mishra (Elementary Education Online, 2019)
This paper analyzes the different factors of attrition in Indian private Insurance companies and the employee retention strategies which are being adopted by these companies. This study is based on secondary as well as primary data. There is a cut throat competition in the Insurance companies. So, the workforces face a tremendous pressure to achieve its targets and if they couldn’t achieve the targets, either organization terminates them or they leave the job on their own. No organization can stay away from attrition and Insurance sector is also not an exception. Even Insurance sector is facing higher rate of attrition just after the IT and ITES companies. Attrition is considered good upto an extent. When it is good it may provide a platform of exchange of new ideas among the employees. It may help the organization to achieve its predetermined goal and many more advantages attached to it. But, when attrition reaches the upper limit it left the organization nowhere. Detailed empirical study highlight the recommendations for improving the attrition rate and suggest how employers can improve the retention of employees with full job satisfaction and improved target achievements. It is the study of an economic management of private insurance companies in India.